2020
DOI: 10.7150/thno.40098
|View full text |Cite
|
Sign up to set email alerts
|

Bax inhibitor 1 preserves mitochondrial homeostasis in acute kidney injury through promoting mitochondrial retention of PHB2

Abstract: Bax inhibitor-1 (BI1) conveys anti-apoptotic signals for mitochondria while prohibitin 2 (PHB2) is implicated in sustaining mitochondrial morphology and function. However, their regulatory roles in acute kidney injury (AKI) are largely unknown.Methods: In human patients with AKI, levels of BI1 in urine and plasma were determined using ELISA. An experimental model of AKI was established using ATP depletion-mediated metabolic stress and ischemia-reperfusion injury (IRI) in primary tubule cells and BI1 transgenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
86
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(91 citation statements)
references
References 63 publications
(73 reference statements)
0
86
0
Order By: Relevance
“…Necrosis was evaluated using MTT assay and LDH release assay with commercial kits (G020-1-1 and G020-2-2) from Jiancheng Biotech (Nanjing, China) ( 46 ).…”
Section: Methodsmentioning
confidence: 99%
“…Necrosis was evaluated using MTT assay and LDH release assay with commercial kits (G020-1-1 and G020-2-2) from Jiancheng Biotech (Nanjing, China) ( 46 ).…”
Section: Methodsmentioning
confidence: 99%
“…This could provide critical insights in regarding mitophagy modulation as a therapeutic intervention for AKI. Likewise, Wang et al (2020a) unveiled that Bax inhibitor-1 (BI1) promotes mitochondrial retention of PHB2 and improves mitophagy, preserving mitochondrial homeostasis in a murine AKI model. As previous studies demonstrated, PHB2 mediates mitophagy once it is externalized to the OMM (Wei et al, 2017;Xiao et al, 2018), this finding indicates that BI1-PHB2 interaction may prevent PHB2 from exporting into cytoplasm, representing a novel mechanism for mediating mitophagy by mitochondria-localized PHB2, rather than total PHB2.…”
Section: Mitophagy and Akimentioning
confidence: 99%
“…Several reports have demonstrated that mitochondrial dysfunction contributes to both acute and CKDs [39][40][41][42] . By utilizing TEM, we examined the mitochondrial fission in renal tubular epithelial cells.…”
Section: Blockade Of Autophagy Alleviates Mitochondrial Fission In Hymentioning
confidence: 99%